PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN J&T EXPRESS BLANGKEJEREN - Henny Sueni Sueni; Permana Honneyta Lubis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aims to examine the effect of Service Quality and Price on Customer Satisfaction and Its Impact on Customer Loyalty JT Express Blangkejeren. Sampling method on this research using Purposive Sampling with samples of 100 respondents. Path Analysis is used as an analytical method to determine the effect of all the variables involved. The results of this study indicate that the variables of Service Quality and Price variables have a significant effect on Consumer Satisfaction. And price variables have a significant effect on Customer Loyalty. Furthermore, Customer Satisfaction variables mediate partially between the Service Quality and Price on Customer Loyalty.